2013
DOI: 10.1017/s0022215113002041
|View full text |Cite
|
Sign up to set email alerts
|

Elasticated retractors in tracheostomy

Abstract: We present a novel way of providing and improving retraction whilst performing tracheostomies, using elasticated retractors. The benefits of this method include an improved surgical field and the facility for use by a single surgeon. This type of retraction could potentially be used in a variety of other head and neck procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…After the initial skin incision is made for access, the fishhook elasticated retractors (5 mm Lone Star Elastic Stays, Cooper Surgical) are positioned in a similar manner to that described previously by Steele and Mountain (1), with the hook of the retractors secured in the skin edges and attached to the surgical drapes using mosquito clips. As the dissection is deepened the hook position can be deepened sequentially without unnecessary, cumbersome additional movement and, importantly, without loss of exposure.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After the initial skin incision is made for access, the fishhook elasticated retractors (5 mm Lone Star Elastic Stays, Cooper Surgical) are positioned in a similar manner to that described previously by Steele and Mountain (1), with the hook of the retractors secured in the skin edges and attached to the surgical drapes using mosquito clips. As the dissection is deepened the hook position can be deepened sequentially without unnecessary, cumbersome additional movement and, importantly, without loss of exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, these retraction devices can obscure the view of the trainer in such procedures and can hamper the ability of trainers to supervise trainee surgeons effectively during surgical dissection and anastomosis formation (rigid sided, deep wound). This report describes the use of ‘fish-hook’ elasticated retractors that have been previously described for use in ENT (1), maxillo-facial (2), hand (3), gynaecological (4) and trans-anal surgery (5).…”
Section: Introductionmentioning
confidence: 99%
“…Patients undergoing surgical tracheostomy tend to have unfavourable anatomy, which has implications for training. 2 With the procedure becoming more commonplace, there could be a tendency to underplay the potential complications. The review found that complications were common, both in the critical care and ward environment, occurring in just over 20 per cent of cases.…”
Section: Focus On Tracheostomymentioning
confidence: 99%
“…Surgical tracheostomy continues to be undertaken on those patients unsuitable for percutaneous techniques. Patients undergoing surgical tracheostomy tend to have unfavourable anatomy, which has implications for training 2 . With the procedure becoming more commonplace, there could be a tendency to underplay the potential complications.…”
mentioning
confidence: 99%